EVALUASI PELAKSANAAN KEBIJAKAN BUS RAPID TRANSIT TRANS SEMARANG KORIDOR I JURUSAN MANGKANG - PENGGARON - Albertus Yose Satria; Kismartini Kismartini; Dyah Lituhayu (Journal of Public Policy and Management Review, 2015)
Semarang City Government through Perda No. 8 of 2008 on the medium -term Development Plan (RPJMD ) Semarang for years 2010-2015 regulates the provision of Bus Rapid Transit Trans Semarang number 4 corridor . Bus Rapid Transit service availability Trans Semarang as the responsibility for the fulfillment of the infrastructure by the Government of Semarang in terms of mass transportation in the city of Semarang . Trans Semarang BRT corridor I Mangkang majors - Penggaron already underway in October 2010.Tujuan of BRT Trans Semarang itself which is to parse the numbers congestion and reduce the number of accidents in the city of Semarang . Evaluation is needed in this policy to determine the extent of implementation of the Bus Rapid Transit policy is to provide benefits for the citizens in the city of Semarang by using the criteria of evaluation criteria William M Dunn . Namely : effectiveness , efficiency , adequacy , grading , responsiveness , accuracy . Policy implementation Bus Rapid Transit corridor Trans Semarang I where in the evaluation criteria , 5 of them are still considered not good and the result is not in accordance with the original plan that is based on effectiveness , efficiency , adequacy , grading , responsiveness and accuracy of the activity . There are various obstacles in its implementation such as the quality and quantity of the main means BRT bus fleet itself , then the main means lack of care and support and also the lack of cooperation of compact between parties related too. Overall the number of assessments have not been good in the evaluation criteria , the implementation of the Trans Semarang BRT corridor which I have been running since October 2010 has yet to be declared successful . The recommendation for this program such as increasing the number of bus fleet to improve the quality and quantity of the implementation of the BRT itself , , BLU UPTD Terminal Mangkang and PT Trans Semarang.